A Social Determinant of Health May Modify Genetic Associations for Blood Pressure: Evidence From a SNP by Education Interaction in an African American Population - Hollister, Brittany M.; Farber-Eger, Eric; Aldrich, Melinda C.; Crawford, Dana C. (Frontiers in Genetics, 2019)
African Americans experience the highest burden of hypertension in the United States compared with other groups. Genetic contributions to this complex condition are now emerging in this as well as other populations through large-scale genome-wide association studies and meta-analyses. Despite these recent discovery efforts, relatively few large-scale studies of blood pressure have considered the joint influence of genetics and social determinants of health despite extensive evidence supporting their impact on hypertension. To identify these expected interactions, we accessed a subset of the Vanderbilt University Medical Center biorepository linked to de-identified electronic health records of adult African Americans genotyped using the Illumina Metabochip (n=2,577). To examine potential interactions between education, a recognized social determinant of health, and genetic variants contributing to blood pressure, we used linear regression models to investigate two-way interactions for systolic and diastolic blood pressure. We identified a two-way interaction between rs6687976 and education affecting diastolic blood pressure (p=0.052). Individuals homozygous for the minor allele and having less than a high school education had higher diastolic blood pressure compared with 1) individuals homozygous for the minor allele and high school education or greater and 2) individuals not homozygous for the minor allele and less than a high school education. To our knowledge, this is the first electronic health record-based study to suggest a gene-environment interaction for blood pressure in African Americans, supporting the hypothesis that genetic contributions to hypertension may be modulated by social factors.